2023
DOI: 10.1037/tra0001149
|View full text |Cite
|
Sign up to set email alerts
|

PTSD, depression, and suicidality among survivors of childhood sexual trauma (CST), military sexual trauma (MST), and sexual revictimization (CST + MST).

Abstract: Objective: Research to date has not examined how childhood sexual trauma (CST) followed by sexual trauma during military service (MST) relates to posttraumatic stress disorder (PTSD), depression, and suicidality among women and men. Given the strong association between MST in particular, and these serious posttraumatic outcomes, the current study sought to address this gap. Method: The current study compared the mental health concerns of 268 treatment-seeking veterans who were survivors of CST, MST, or both (C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
10
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 16 publications
(14 citation statements)
references
References 63 publications
(87 reference statements)
4
10
0
Order By: Relevance
“…These results suggest that exposure to multiple trauma types does not necessarily summate to greater reported PTSD and depression symptoms. Although some literature supports the cumulative effects of multiple trauma types on psychological symptoms (Baca et al, 2021;Scott et al, 2014), our findings corroborate past studies that have also been unable to find these differences (Walter et al, 2014;Wolfe-Clark et al, 2017). It is possible that sex differences in study samples may partly explain these discrepant findings.…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…These results suggest that exposure to multiple trauma types does not necessarily summate to greater reported PTSD and depression symptoms. Although some literature supports the cumulative effects of multiple trauma types on psychological symptoms (Baca et al, 2021;Scott et al, 2014), our findings corroborate past studies that have also been unable to find these differences (Walter et al, 2014;Wolfe-Clark et al, 2017). It is possible that sex differences in study samples may partly explain these discrepant findings.…”
Section: Discussionsupporting
confidence: 91%
“…It is possible that sex differences in study samples may partly explain these discrepant findings. Among study samples that have found cumulative effects of trauma type, they have been found in primarily or entirely female samples (Baca et al, 2021; Scott et al, 2014), although this is not always the case (Walter et al, 2014). Conversely, studies that have not found this effect have typically had primarily male samples (such as the present study; Wolfe-Clark et al, 2017).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…To our knowledge, this study is the first to examine both the independent and interactive associations of CSA and MST with different types of suicidal thoughts and behaviors, including past and self-reported likelihood of future behaviors, in a nationally representative sample of US military veterans. Consistent with some past findings (Baca et al, 2021;Holliday et al, 2021;Kelly et al, 2011), veterans who experienced both CSA and MST, relative to those who experienced neither, were at greater risk for reporting experiences of suicidal ideation in the past year, lifetime suicide attempt, and likelihood of making a future suicide attempt. This finding persisted above and beyond a variety of correlates of suicide risk previously documented in the literature (e.g., non-CSA ACEs, combat exposure, psychiatric comorbidity, gender), as well as CSA and MST individually.…”
Section: Discussionsupporting
confidence: 84%
“…To date, examination of sexual violence revictimization across the lifespan in relation to suicidal self-directed violence risk among veterans remains limited. The few available studies suggest that veterans who have experienced sexual revictimization (i.e., CSA and MST) are at greater risk for psychiatric symptoms and suicidal self-directed violence (Baca et al, 2021; Holliday et al, 2021; Kelly et al, 2011). However, prior research has largely focused on small convenience samples and discrete timepoints of exposure (e.g., childhood or during military service).…”
Section: Introductionmentioning
confidence: 99%